Safety and Effectiveness of Coronary Angiography or Intervention through the Distal Radial Access: A Meta-Analysis - Jun Cao (Hindawi-Wiley, 2021)
Objectives. Searching the literature for coronary angiography (CAG) or intervention through distal radial access (DRA) and performing a meta-analysis. Background. Coronary angiography (CAG) or intervention through distal radial access (DRA) may have a similar success rate, low radial artery occlusion rate, low radial artery spasm rate, and low rate of puncture site hematoma for patients with coronary heart disease. Therefore, the randomized controlled trials (RCTs) were searched, and the data were pooled for meta-analysis to evaluate the effectiveness and safety of DRA. Methods. RCTs comparing the CAG or intervention through DRA vs. transradial access (TRA) published between January 1, 2017, and May 4, 2021, were searched in the PubMed, Embase, and Cochrane databases. The endpoints included the rate of access success and the number of radial artery occlusions, radial artery spasms, and puncture site hematomas. The data were extracted, and a random-effects model was used for analysis. Results. Among 204 studies, 6 RCTs (with 2825 participants) met the inclusion criteria. Compared to TRA, the access success rate in DRA (p=0.1) and the lower rate of puncture site hematoma were not significantly different (p=0.646), while the radial artery occlusion rate (p<0.001) and radial artery spasm rate (p=0.029) were significantly lower. Conclusion. In summary, DRA has a similar access success rate and incidence of hematoma at the puncture site, but a lower incidence of RAO and spasm compared to TRA. These findings demonstrated that DRA is a safe and effective access for CAG or intervention.